Analysis of Household Solid Waste Management Around the Opak Chips Factory, Tuntungan Village II Kutalimbaru Deli Serdang District - Nanda, Meutia; Syahrani, Putri; Alvi Nur Ilmi Br Ginting; Anna Kholijah; Salsabila Audina (Universitas Muhammadiyah Palu, 2024)
According to the Ministry of Environment and Forestry, waste is the remainder of a business or activity. Solid waste is residual or discarded material in solid form resulting from various human activities. Deli Serdang Regency produces many opaque chips. Tuntungan II Village is one of the cassava growing center villages in Deli Serdang Regency, North Sumatra Province. The availability of cassava raw materials has implications for community activities with small and medium enterprises. From the initial observation survey of the opaque chips management process, it was found that residual material resulting from production or waste was in solid form. Solid waste arises from the management or disposal of waste from industrial activities. Solid industrial waste can be organic waste or inorganic waste. The aim of this research is to see an overview of solid waste management at the opaque chips factory in Tuntungan II Village, Kutalimbaru Deli Serdang District. The method in this research uses qualitative methods with descriptive research, data collection by direct observation, in-depth interviews, and documentation. The results obtained from this research are that this opaque chips factory produces solid waste in the form of leftover cassava pulp and cassava peel. Cassava pulp and cassava skin will be dried first before being given to farmers as animal feed, this is of course an effort to reduce the impact of waste management so that it does not pollute the surrounding environment. Solid waste at this opaque chips factory is processed well. The suggestion in this research is that the role of the government and the community is to provide outreach to the community and it is hoped that they can supervise work at the opaque chips factory regarding waste management.